Study the Effect of Graphene on the Contact Angle, Water Absorption and Thermal Stability ( TGA ,DSC) for Blend (Epoxy & Repcoat ZR) - Hassin, Mena M.; Hussein, Seenaa I. (Iraqi Journal of Physics, 2021)
In this study, polymeric coating was developed by incorporating nano graphene in the polymer blend with applications to oil storage tanks. The oil storage tanks samples were brought from the oil Pipeline Company / Doura refinery in Baghdad. The coating polymer was formed with a blend (epoxy resin and repcoat ZR). The proportion of mixing the mixture was 3:1:1 epoxy resin 21.06 gm: repcoat ZR 10.53 gm: hardener 10.53 gm. The blend/graphene was prepared using in stui-polymerization method with different weight percentage 1, 3, 5, and 7 wt % added to blend. The resulting solution was put in a glass tube on a magnetic stirrer for one hour at a temperature of 40 °C. The result of contact angle and water absorption the best ratio of 3wt % (73.46). The current work confirms that the thermal stability of the nanocomposites increases gradually with increasing the percentage of Gr compared to the blend without adding Gr nano and this is due to the thermal resistance of the Gr nano.